2017
DOI: 10.1007/s11356-017-0797-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of hydro-biofuel-wind energy consumption on environmental cost of doing business in a panel of BRICS countries: evidence from three-stage least squares estimator

Abstract: The renewable energy sources are considered the vital factor to promote global green business. The environmental cost of doing business is the pre-requisite to analyze sustainable policies that facilitate the eco-minded entrepreneurs to produce healthier goods. This study examines the impact of renewable energy sources (i.e., hydro energy, biofuel energy, and wind energy) on the environmental cost of doing business in a panel of BRICS (Brazil, Russian Federation, India, China, and South Africa) countries, for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The study has a wider research contribution in the existing available research work, which shows the strong appearance in green supply chain management (GSCM) literature, i.e., the previous studies limited to primary research by using different manufacturing firm's data and evaluated the perceived value of line managers and different stakeholders about GSCM practices, reverse logistics, sustainable supply chain, etc., and linked up with policy inferences (see, Zhu and Sarkis 2004, Zhu et al 2008, Green et al 2012, Mitra and Datta 2014, Zhu et al 2017, Kaur et al 2018, while some other studies only limited to confined by few socio-economic and environmental factors with GSCM practices, including, green purchasing and eco-designing (see, Khan et al 2017b, Khan andQianli, 2017), FDI, industrialization, energy demand (see, Zaman and Shamsuddin 2017), carbon-fossil-GHG emissions (see, Khan et al 2017a). The previous literature is filled by numerous logistics indices, including, institutional and operational performance indices , supply chain functions (Green Jr. et al 2008), reverse logistics (Sbihi and Eglese, 2010), competitiveness (Rao and Holt, 2005), green innovations (Lin and Ho, 2008), regulatory control and green practices (Lin and Ho, 2011), green product designing (Wang, 2018), non-green energy sources (Khan et al 2018), environmental cost of doing business (Zaman, 2018), environmental sustainability (Wang et al 2017), green logistics (Arslan and Sar, 2017), etc.…”
Section: Research Contribution(s) and Objectives Of The Studymentioning
confidence: 99%
“…The study has a wider research contribution in the existing available research work, which shows the strong appearance in green supply chain management (GSCM) literature, i.e., the previous studies limited to primary research by using different manufacturing firm's data and evaluated the perceived value of line managers and different stakeholders about GSCM practices, reverse logistics, sustainable supply chain, etc., and linked up with policy inferences (see, Zhu and Sarkis 2004, Zhu et al 2008, Green et al 2012, Mitra and Datta 2014, Zhu et al 2017, Kaur et al 2018, while some other studies only limited to confined by few socio-economic and environmental factors with GSCM practices, including, green purchasing and eco-designing (see, Khan et al 2017b, Khan andQianli, 2017), FDI, industrialization, energy demand (see, Zaman and Shamsuddin 2017), carbon-fossil-GHG emissions (see, Khan et al 2017a). The previous literature is filled by numerous logistics indices, including, institutional and operational performance indices , supply chain functions (Green Jr. et al 2008), reverse logistics (Sbihi and Eglese, 2010), competitiveness (Rao and Holt, 2005), green innovations (Lin and Ho, 2008), regulatory control and green practices (Lin and Ho, 2011), green product designing (Wang, 2018), non-green energy sources (Khan et al 2018), environmental cost of doing business (Zaman, 2018), environmental sustainability (Wang et al 2017), green logistics (Arslan and Sar, 2017), etc.…”
Section: Research Contribution(s) and Objectives Of The Studymentioning
confidence: 99%
“…The economy strives hard to combat the environmental evils with sustainable instruments that hope to recover the economy in coming years [2]. The vast literature is available on WEF's nexus and environmental related issues, that is, (i) biodiversity loss [3], (ii) renewable energy-biofuel energy [4], (iii) Transport emissions [5], (iv) WEF's nexus [6], (v) green logistics [7], (vi) sustainable tourism [8], (vii) health issues [9], and (viii) financial development [10]. These studies confirmed the volatility of climate change in different socio-economic environment across the globe.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Naz et al [80] highly promoted the importance of RE demand in mitigating carbon emissions in the presence of FDI inflows and continued EG. Zaman [81] emphasized the need to use wind-hydro-biofuel energy demand in order to promote green business. Apergis et al [82] suggested the need to reinvest carbon money in healthcare infrastructure and RE-associated projects, which would help sustain the country's EG.…”
Section: Resultsmentioning
confidence: 99%